PENGARUH KONSENTRASI MINALIT DAN JENIS KAYU TERHADAP SIFAT RETENSI DAN KETAHANAN API (The effect of minalits concentrstion and wood species on retention and fire resistance properties) - Tjutju Nurhayati; Suprapto Suprapto (Jurnal Penelitian Hasil Hutan, 1993)
The aim of this experiment is to investigate the use of minalith as fire retardant which is able to reach the higher grade of fire resistance for karet (hevea brasilliensis), meranti merah (shore asp.) and tusam wood (pinus merkusii). The minalith protection on wood was done at 15%, 19% and 23% concentrations by hot soaking at 60-70°C for 6 hours, followed by cold soaking at room temperature for 5 days periods. The characteristics tested were retention, heat release, smoke density and temperature deviation.The result showed that the highest retention was obtained from meranti merah (41.0 – 59.9 kg/m3) and the lowest one was from tusam (37,0 – 47.2 kg/m3). Higher concentration on each wood species produces higher retention. In terms of smoke density and temperature deviation, the difference was very significant between non-protected wood. Heat release of protected tusam was the best (4 - 139°C minute). At 19% and 23% minalith concentrations, tusam showed the quality on fairly combustible while other protected wood were on fire retarding and fairly retarding classification. The highest fire resistance properties was shown by tusam at the 23% minalith concentration.